Analisis Implementasi Augmented Reality Pada Bidang Pendidikan: Systematic Literature Review - Yeremia, Deryl Andeya; Chang, Jonathan Christian Teofilus (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze how Augmented Reality technology is implemented in educational environments, evaluate the benefits and constraints faced, and provide recommendations for optimizing its use. With this analysis, it is expected to contribute to the development of more adaptive and effective technology-based educational innovations in the digital era. The Systematic Literature Review (SLR) approach used in this study. The SLR method is a research design that aims to answer research questions by synthesizing evidence from previous studies. The results of the study show that Augmented Reality (AR) has great potential to be applied in education in 2021–2025 because it is able to present interactive, interesting, and easily accessible learning via mobile devices. AR has been shown to increase motivation, conceptual understanding, and student learning outcomes through visualization of material in 3D. Thus, the implementation of AR is a strategic step in improving the quality of learning in the digital era.